Comparison of the luteal phase estradiol priming stimulation and standard antagonist protocols in patients with diminished ovarian reserve undergoing ICSI - Ertürk Aksakal, Sezin; Aldemir, Oya; Kahyaoğlu, İnci and Kaplanoğlu, İskender and Dilbaz, Serdar (Journal of Surgery and Medicine, 2022)
Background/Aim: No consensus on the optimal stimulation protocol for increasing in vitro fertilization (IVF) treatment’s success rate in patients with diminished ovarian reserve is available. This study aimed to compare IVF outcomes in patients with diminished ovarian reserve (DOR) stimulated with a luteal phase estradiol (E2) priming protocol versus the standard antagonist protocol. Methods: This retrospective cohort study included 603 patients who underwent intracytoplasmic sperm injection cycles (ICSI) after the diagnosis of DOR and who were stimulated with the luteal E2 priming protocol (E2 priming group; n = 181) or the standard antagonist protocol (antagonist group; n = 422). Groups were compared in terms of demographic characteristics, ovarian stimulation results, ICSI cycle outcomes, clinical pregnancy, and live birth rates per embryo transfer. Results: The duration of ovarian stimulation was longer, and the total gonadotropin dose used was significantly higher (P = 0.001) in the E2 priming group than in the antagonist group. The number of embryos transferred was higher in the antagonist group when compared with E2 priming group (0.87 (0.75) versus 0.64 (0.49); P = 0.01), but no statistically significant difference in terms of embryo quality between groups was found (P > 0.05). The cycle cancellation rate, clinical pregnancy, and live birth rates per embryo transfer were similar in both groups. Conclusions: No difference between IVF outcomes in the patients diagnosed with DOR who were stimulated with the antagonist protocol and the luteal E2 priming protocol was detected. The antagonist protocol might be considered more advantageous because of the shorter treatment duration and lower doses of gonadotropin. This protocol also allows more embryos to be transferred. Additional randomized controlled trials are needed to verify these findings.